Agonistic behavior of Nasutitermes sp. (Isoptera: Termitidae) - Buschini, Maria Luisa T.; Leonardo, Ana Maria C. [UNESP] (My University, 2001)
The possible existence of agonistic, intraspecific behavior, and polycalic nests was investigated for Nasutitermes sp. Aggressive tests among soldiers, workers and between soldiers and workers of different nests were carried out, and later, injury percentage was analyzed from the results of such tests. Agonistic behavior was observed in the majority of the experiments performed between individuals from different colonies. In the light of such results, it was assumed that polycalism does not exist among the nests of this species.
Keywords: Aggression; Agonistic behavior; Brazil; Insecta; Isoptera; Termites